Unmet Nonmedication Needs After Hospital Discharge and Adverse Outcomes Among Acute Respiratory Failure Survivors in Brazil: A Prospective Feasibility Study - Sérgio R. R. Decker, MD, MSc; Danielle do A. Pereira, BSc; Gabriela S. Rech, MSc; Rosa da R. M. dos Santos, MSc; Denise de Souza, MSc; Raíne F. De Carli, PhD; Geraldine Trott, PhD; Ana P. de Souza, PhD; Janine Gonzaga, BSc; Lauren S. Costa, MSc; Jonas M. Wolf, PhD; Gregory S. Medeiros, MD, PhD; et al. (Critical Care Explorations, 2025)
IMPORTANCE:. In-hospital survivorship for acute respiratory failure has improved, but unmet nonmedication healthcare needs may contribute to adverse events post-discharge. OBJECTIVES:. To evaluate the feasibility of characterizing early unmet nonmedication discharge needs, classified as durable medical equipment (DME), home health services (HHS), and follow-up medical appointments (FUA) for acute respiratory failure survivors in Brazil. Secondary objectives include describing the profile of needs, unmet needs, and adverse outcomes post-discharge. DESIGN:. Prospective feasibility cohort study, with enrollment between October 2020 and March 2021. SETTING:. One tertiary teaching hospital from Southern Brazil with 76 ICU beds. PARTICIPANTS:. Adult survivors from acute respiratory failure who were discharged home. MAIN OUTCOMES AND MEASURES:. Our primary outcome was the feasibility of measuring unmet nonmedication needs between 7 and 28 days post-discharge, considering greater than 80% of data completeness as feasible. Secondary outcomes included the characterization of needs and needs unmet per type at 1 month and the crude risk of all-cause death, hospital readmission, and urgent visits to the emergency department at 3 months post-discharge. RESULTS:. Of 337 patients screened, 72 were enrolled, and data on unmet nonmedication needs were collected from 66 patients, resulting in a primary feasibility outcome of 91.7%. The median age was 59 years, 38.9% were female, most were self-declared White, and were employed before admission. During the index admission, 87.3% were diagnosed with COVID-19, and 79.2% received invasive mechanical ventilation. The frequency of nonmedication discharge needs was 48 (72.7%) for DME, 54 (81.8%) for HHS, and 60 (90.9%) for FUA. At 1 month, 36 (58.1%) had at least one need unmet; at 3 months, 12 (19.0%) had at least one adverse outcome. CONCLUSIONS AND RELEVANCE:. Detailed measurement of nonmedication needs post-discharge for acute respiratory failure survivors in Brazil is feasible. Unmet nonmedication needs are a common problem to be addressed in this population.